RAPID IL-6 REDUCTION AS A POTENTIAL PHENOTYPE FOR EARLY HEMODYNAMIC IMPROVEMENT DURING COMBINED OXIRIS AND HA330 HEMOADSORPTION IN SEPTIC SHOCK (Vietnam Journal of Community Medicine, 2026)
Objective: To describe early hemodynamic, metabolic, inflammatory, and organ dysfunction trajectories during the first 48 hours of combined oXiris-HA330 hemoadsorption in septic shock patients requiring continuous renal replacement therapy (CRRT), and to explore whether rapid interleukin-6 (IL-6) reduction may identify a potential responder phenotype. Subjects and Methods: This prospective single-center observational study included 31 adult patients with septic shock requiring CRRT who received combined oXiris-HA330 hemoadsorption. Clinical and laboratory variables were collected at baseline, 24 hours, and 48 hours after treatment initiation. Rapid IL-6 response was defined as a ≥50% reduction at 24 hours compared with baseline. Results: Thirty-one patients with septic shock requiring CRRT received combined oXiris-HA330 hemoadsorption. During the first 48 hours, mean arterial pressure increased, while vasoactive-inotropic score decreased significantly. Lactate, base excess, IL-6, and procalcitonin also improved over time (all p < 0.01). Patients with rapid IL-6 reduction were more likely to receive treatment within 12 hours after septic shock diagnosis (61.1% vs. 23.1%, p = 0.036) and showed lower vasoactive requirements and lower observed 28-day mortality than non-responders (5.6% vs. 69.2%, p < 0.001). Conclusion: Combined oXiris-HA330 hemoadsorption was associated with favorable early hemodynamic and inflammatory trajectories in septic shock patients requiring CRRT. Rapid IL-6 reduction may represent a potential biological responder phenotype associated with more favorable clinical trajectories. These exploratory findings require validation in larger controlled studies.
Keywords: Septic shock; CRRT; blood purification; cytokine adsorption; oXiris membrane; HA330 hemoadsorption.